Stuck Outside and Inside: An Exploratory Study on the Effects of the COVID-19 Outbreak on Italian Parents and Children’s Internalizing Symptoms - Crescentini, Cristiano; Feruglio, Susanna; Matiz, Alessio; Paschetto, Andrea; Vidal, Enrico; Cogo, Paola; Fabbro, Franco (Frontiers in Psychology, 2020)
The Covid-19 outbreak and the subsequent lockdown have profoundly impacted families’ daily life, challenging their psychological resilience. Our study aimed to investigate the immediate psychological consequences of the pandemic on Italian parents and children focusing on internalizing and post-traumatic symptoms. We also wanted to explore the impact of possible risk and resilience factors, e.g. lifestyle and behaviours, emotional and cognitive beliefs, on parents and children’s reaction to the emergency distress. An online survey was administered during the country's nationwide lockdown to 721 Italian parents of at least one child aged between 6-18 years. The respondent completed the survey for himself/herself and his/her child. The survey included socio-demographic items and validated questionnaires on parents' post-traumatic stress symptoms, depression and anxiety levels, and on children's internalizing problems. Parents were asked to fill the questionnaires twice: once referring to the current emergency condition and once recalling how they and their child felt a few months before Covid-19 outbreak. Multiple regression analyses showed that specific demographic characteristics (i.e., sex and age) and psychological factors of children and parents, such as fear of contagion and the opportunity to think about possible secondary positive effects of the pandemic, had a predictive value on the presence of internalizing symptoms of both parents and children. Moreover, parents’ behaviours during the lockdown period (i.e., employment status and sport practiced) were significantly related to their own internalizing symptoms; these symptoms, in turn, had a strong and positive predictive value on children’s internalizing problems. Besides, analyses of variance showed that internalizing symptoms of parents and children were significantly higher during the Covid-19 pandemic than before it started. In addition to showing a direct effect of the pandemic on the psychological health of parents and children, the present results also give a series of important information on how parents perceive, and therefore influence, their children in this period of emergency. Our findings thus highlight the urgent need to provide parents with adequate support to take care of their own psychological wellbeing and to help their children coping with the direct and indirect effects of the pandemic.